Pressure-sensitive adhesive composition for optical members and optical member with pressure-sensitive adhesive layer
The adhesive composition with a (meth)acrylic copolymer and hydroxyl-containing components forms a pseudo-crosslinked structure to prevent shrinkage and corrosion, addressing polarizing plate issues in liquid crystal displays.
Patent Information
- Application Number
- JP2021055541
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-03-29
AI Technical Summary
Polarizing plates in liquid crystal display devices experience shrinkage due to temperature changes, leading to warpage and display unevenness, especially in frameless smartphones and tablets with larger plates, and existing adhesives can corrode transparent conductive films over time.
An adhesive composition comprising a (meth)acrylic copolymer with 0.1% to 5.0% hydroxyl groups, an isocyanate crosslinking agent, and a tackifier with hydroxyl groups, forming a pseudo-crosslinked structure that suppresses shrinkage and prevents corrosion, with a gel fraction of 70% to 90%.
The adhesive composition effectively suppresses polarizing plate shrinkage at high temperatures and prevents corrosion of transparent conductive films, ensuring excellent adhesion and processability.
Smart Images

Figure 0007600015000001 
Figure 0007600015000002 
Figure 0007600015000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a pressure-sensitive adhesive composition and an optical member with a pressure-sensitive adhesive layer. [Background technology]
[0002] Many portable electronic devices such as smartphones and tablet terminals incorporate liquid crystal display devices. In general, liquid crystal display devices include a liquid crystal cell in which a liquid crystal layer is sandwiched between two glass substrates, and polarizing plates disposed on both sides of the liquid crystal cell. In order to ensure the visibility of the liquid crystal display device, the liquid crystal cell and the polarizing plates are generally bonded together via an adhesive layer formed of an acrylic adhesive.
[0003] For example, Patent Document 1 discloses a pressure-sensitive adhesive composition for optical members, which contains, as monomer units, a (meth)acrylic polymer having a weight average molecular weight of 1,000,000 or more and containing 50% by weight or more of an alkyl (meth)acrylate having an alkyl group having 4 or more carbon atoms and 0.2 to 10% by weight of an unsaturated carboxylic acid, 0.01 to 5 parts by weight of an aliphatic and / or alicyclic isocyanate crosslinking agent relative to 100 parts by weight of the (meth)acrylic polymer, 0.02 to 2 parts by weight of a peroxide relative to 100 parts by weight of the (meth)acrylic polymer, and 0.01 to 1 part by weight of a silane coupling agent relative to 100 parts by weight of the (meth)acrylic polymer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4485329 Summary of the Invention [Problem to be solved by the invention]
[0005] Generally, polarizing plates are formed by laminating members with different shrinkage rates, and therefore are prone to shrinkage due to temperature changes. This tendency becomes more pronounced as the size of the polarizing plate increases. In addition, in recent years, small monitors used in smartphones, tablet terminals, etc. have become increasingly frameless, and polarizing plates larger than before are increasingly used. The shrinkage of polarizing plates can cause warping of display panels, display unevenness, dimensional accuracy, and the like. For this reason, the adhesive composition used in polarizing plates is required to be able to form an adhesive layer capable of suppressing the shrinkage of polarizing plates that may occur when exposed to a high temperature (e.g., 85°C; the same applies below) environment. In order to suppress the shrinkage of the polarizing plate by the adhesive layer, it is considered to increase the cohesive force of the adhesive layer. For example, a method of increasing the cohesive force of the adhesive layer can be mentioned, which increases the amount of carboxyl groups in the (meth)acrylic polymer contained in the adhesive composition. For example, the adhesive composition described in Patent Document 1 contains a (meth)acrylic polymer containing an unsaturated carboxylic acid as a monomer unit, thereby increasing the cohesive force of the adhesive layer formed. However, when a pressure-sensitive adhesive composition containing a (meth)acrylic polymer with many carboxy groups is used to bond a polarizing plate to a liquid crystal cell having a transparent conductive film on its surface, such as an ITO (indium-tin oxide) film, a problem may arise in that the transparent conductive film corrodes over time.
[0006] An object of one embodiment of the present disclosure is to provide a pressure-sensitive adhesive composition capable of suppressing shrinkage of a substrate that may occur when exposed to a high-temperature environment and capable of forming a pressure-sensitive adhesive layer that is unlikely to corrode a transparent conductive film. The problem to be solved by another embodiment of the present disclosure is to provide an optical component with a pressure-sensitive adhesive layer, which can suppress shrinkage of the optical component that may occur when exposed to a high-temperature environment, and which has a pressure-sensitive adhesive layer that is less likely to corrode a transparent conductive film. [Means for solving the problem]
[0007] Specific means for solving the problems include the following aspects. <1> a (meth)acrylic copolymer containing 0.1% by mass to 5.0% by mass of structural units derived from monomers having a hydroxyl group relative to all structural units, and not containing structural units derived from monomers having a carboxy group, or containing structural units derived from monomers having a carboxy group in an amount of more than 0% by mass to 2.0% by mass or less relative to all structural units; An isocyanate-based crosslinking agent; A tackifier having a hydroxyl group; Including, the content of the isocyanate-based crosslinking agent is 0.1 parts by mass to 4.0 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer, the content of the tackifier having a hydroxyl group is 1 part by mass to 20 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer, A pressure-sensitive adhesive composition having a gel fraction after crosslinking of 70% by mass to 90% by mass. <2> The ratio of the mass of the tackifier having a hydroxyl group to the mass of the isocyanate-based crosslinking agent is 2.5 to 100. <1> The pressure-sensitive adhesive composition according to claim 1. <3> The tackifier having a hydroxyl group is at least one compound selected from the group consisting of compounds having a rosin skeleton and compounds having a terpene skeleton. <1> or <2> The pressure-sensitive adhesive composition according to claim 1. <4> In addition, it contains a plasticizer. <1> ~ <3> 13. The pressure-sensitive adhesive composition according to claim 12 . <5> An optical member; provided on the optical member, <1> ~ <4> a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of the above items; An optical member with a pressure-sensitive adhesive layer comprising: Effect of the Invention
[0008] According to one embodiment of the present disclosure, there is provided a pressure-sensitive adhesive composition that can suppress shrinkage of a substrate that may occur when exposed to a high-temperature environment and can form a pressure-sensitive adhesive layer that is less likely to corrode a transparent conductive film. According to another embodiment of the present disclosure, there is provided an optical component with a pressure-sensitive adhesive layer, which can suppress shrinkage of the optical component that may occur when exposed to a high-temperature environment, and which has a pressure-sensitive adhesive layer that is less likely to corrode a transparent conductive film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The pressure-sensitive adhesive composition and the pressure-sensitive adhesive layer-attached optical member of the present disclosure will be described in detail below. The following description of the requirements may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment, and can be modified as appropriate within the scope of the purpose of the present disclosure.
[0010] In the present disclosure, a numerical range indicated using "to" means a range that includes the numerical values before and after "to" as the lower limit and upper limit, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.
[0011] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when the adhesive composition contains multiple substances corresponding to each component, the amount of each component in the adhesive composition means the total amount of the multiple substances present in the adhesive composition, unless otherwise specified.
[0012] In the present disclosure, "(meth)acrylic copolymer" means a copolymer in which the content of structural units derived from monomers having a (meth)acryloyl group is 50 mass% or more of all structural units (i.e., all structural units of the (meth)acrylic copolymer).
[0013] In this disclosure, "(meth)acrylic" is a term that encompasses both "acrylic" and "methacrylic", "(meth)acrylate" is a term that encompasses both "acrylate" and "methacrylate", and "(meth)acryloyl" is a term that encompasses both "acryloyl" and "methacryloyl".
[0014] In this disclosure, "n-" means normal, "i-" means iso, "s-" means secondary, and "t-" means tertiary.
[0015] [Adhesive composition] The pressure-sensitive adhesive composition of the present disclosure comprises a (meth)acrylic copolymer containing 0.1% by mass to 5.0% by mass of structural units derived from a monomer having a hydroxyl group, based on all structural units, and containing no structural units derived from a monomer having a carboxy group, or containing structural units derived from a monomer having a carboxy group in an amount of more than 0% by mass to 2.0% by mass or less based on all structural units; an isocyanate-based crosslinking agent; and a tackifier having a hydroxyl group, wherein the content of the isocyanate-based crosslinking agent is 0.1 parts by mass to 4.0 parts by mass based on 100 parts by mass of the (meth)acrylic copolymer, the content of the tackifier having a hydroxyl group is 1 part by mass to 20 parts by mass based on 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction after crosslinking is 70% by mass to 90% by mass. Hereinafter, "a (meth)acrylic copolymer containing 0.1% by mass to 5.0% by mass of structural units derived from monomers having a hydroxyl group, relative to all structural units, and which does not contain structural units derived from monomers having a carboxy group, or which contains structural units derived from monomers having a carboxy group in an amount of more than 0% by mass to 2.0% by mass or less, relative to all structural units" is also referred to as "specific (meth)acrylic copolymer". The pressure-sensitive adhesive composition of the present disclosure can suppress shrinkage of a substrate that may occur when exposed to a high-temperature environment, and can form a pressure-sensitive adhesive layer that is less likely to corrode a transparent conductive film. The reason why the pressure-sensitive adhesive composition of the present disclosure can exhibit such an effect is unclear, but the present inventors speculate as follows, however, the following speculation is not intended to limit the pressure-sensitive adhesive composition of the present disclosure, but is merely an example. The substrate is not particularly limited as long as it can shrink when exposed to a high temperature environment, and examples thereof include a polarizing plate. The transparent conductive film is not particularly limited, and examples thereof include an ITO (indium-doped tin oxide) film, an ATO (antimony-doped tin oxide) film, an FTO (fluorine-doped tin oxide) film, a tin oxide film, and a zinc oxide film.
[0016] In the adhesive composition of the present disclosure, the hydroxyl group in the specific (meth)acrylic copolymer and the isocyanate group of the isocyanate crosslinking agent undergo a crosslinking reaction. At least a part of the tackifier having a hydroxyl group is taken into the interior of the specific (meth)acrylic copolymer (so-called between polymer chains) by an interaction that is thought to be a hydrogen bond between the hydroxyl group in the specific (meth)acrylic copolymer and the hydroxyl group of the tackifier, and then forms a pseudo crosslinked structure with the isocyanate crosslinking agent. That is, in the adhesive composition of the present disclosure, by having the above-mentioned configuration, the crosslinking reaction between the hydroxyl group in the specific (meth)acrylic copolymer and the isocyanate group of the isocyanate crosslinking agent proceeds relatively quickly, and the tackifier and the isocyanate crosslinking agent form a pseudo crosslinked structure between the polymer chains of the specific (meth)acrylic copolymer, so that the cohesive force of the formed adhesive layer is moderately increased and the gel fraction shows a relatively high value. Therefore, it is presumed that the adhesive layer formed by the adhesive composition of the present disclosure can suppress the shrinkage of the substrate that may occur when exposed to a high temperature environment.In addition, in the adhesive composition of the present disclosure, the specific (meth)acrylic copolymer does not contain a carboxy group, or the specific (meth)acrylic copolymer has a small amount of carboxy groups.Therefore, it is presumed that the adhesive layer formed by the adhesive composition of the present disclosure is unlikely to corrode the transparent conductive film. As described above, the pressure-sensitive adhesive composition of the present disclosure can suppress shrinkage of the substrate that may occur when exposed to a high-temperature environment, and can form a pressure-sensitive adhesive layer that is less likely to corrode a transparent conductive film.
[0017] Generally, a pressure-sensitive adhesive composition is required to be capable of forming a pressure-sensitive adhesive layer having excellent adhesion to a substrate. In contrast, a pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure exhibits appropriately high cohesive strength and therefore has excellent adhesion to a substrate.
[0018] In addition, the adhesive layer formed by the adhesive composition of the present disclosure exhibits moderately high cohesive strength and is moderately hard, so that during cutting processing, the adhesive layer (so-called glue) is less likely to adhere to the cutting blade or protrude, and the processability (so-called cutting processability) is also excellent.
[0019] [Specific (meth)acrylic copolymer] The pressure-sensitive adhesive composition of the present disclosure contains a (meth)acrylic copolymer that contains 0.1% by mass to 5.0% by mass of structural units derived from a monomer having a hydroxyl group, relative to all structural units, and does not contain structural units derived from a monomer having a carboxy group, or contains structural units derived from a monomer having a carboxy group in an amount of more than 0% by mass and not more than 2.0% by mass, relative to all structural units [i.e., a specific (meth)acrylic copolymer]. The pressure-sensitive adhesive composition of the present disclosure may contain only one type of specific (meth)acrylic copolymer, or may contain two or more types.
[0020] <Structural Unit Derived from Monomer Having a Hydroxyl Group> The specific (meth)acrylic copolymer contains 0.1% by mass to 5.0% by mass of structural units derived from monomers having a hydroxyl group based on the total structural units. In the present disclosure, a "structural unit derived from a monomer having a hydroxyl group" refers to a structural unit formed by addition polymerization of a monomer having a hydroxyl group.
[0021] The type of the monomer having a hydroxyl group is not particularly limited. An example of a monomer having a hydroxyl group is a monomer having at least one hydroxyl group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.
[0022] Specific examples of monomers having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, 3-methyl-3-hydroxybutyl (meth)acrylate, 1,1-dimethyl-3-hydroxybutyl (meth)acrylate, 1,3-dimethyl-3-hydroxybutyl (meth)acrylate, 2,2,4-trimethyl-3-hydroxypentyl (meth)acrylate, 2-ethyl-3-hydroxyhexyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, glycerin mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, and poly(ethylene glycol-propylene glycol) mono(meth)acrylate. Among these, as the monomer having a hydroxyl group, for example, from the viewpoint of good copolymerizability with other monomers, hydroxyalkyl (meth)acrylates are preferred, and from the viewpoint of good compatibility with other monomers and good reactivity with isocyanate-based crosslinking agents, hydroxyalkyl (meth)acrylates having a hydroxyalkyl group with 1 to 5 carbon atoms are more preferred, hydroxyalkyl (meth)acrylates having a hydroxyalkyl group with 2 to 4 carbon atoms are even more preferred, and 2-hydroxyethyl acrylate (2HEA) is particularly preferred.
[0023] The specific (meth)acrylic copolymer may contain only one type of structural unit derived from a monomer having a hydroxyl group, or may contain two or more types.
[0024] The content of the structural units derived from monomers having a hydroxyl group in the specific (meth)acrylic copolymer is 0.1% by mass to 5.0% by mass based on the total structural units of the specific (meth)acrylic copolymer. When the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 0.1% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the formed pressure-sensitive adhesive layer can suppress the shrinkage of the substrate that may occur when exposed to a high-temperature environment. The reason for this is believed to be that the crosslinking between the specific (meth)acrylic copolymer and the isocyanate-based crosslinking agent proceeds sufficiently, and the cohesive force of the formed pressure-sensitive adhesive layer is sufficiently increased. In addition, when the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 0.1% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the formed pressure-sensitive adhesive layer tends to have excellent processability. From this viewpoint, the content of structural units derived from monomers having a hydroxyl group in the specific (meth)acrylic copolymer is 0.1 mass% or more, preferably 0.2 mass% or more, more preferably 0.3 mass% or more, even more preferably 0.4 mass% or more, and particularly preferably 0.5 mass% or more, based on the total structural units of the specific (meth)acrylic copolymer. When the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 5.0 mass% or less based on the total structural units of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to exhibit good adhesion to the adherend. This is thought to be because the specific (meth)acrylic copolymer and the isocyanate-based crosslinking agent are not crosslinked excessively, and the pressure-sensitive adhesive layer formed exhibits appropriate hardness. From this viewpoint, the content of structural units derived from monomers having a hydroxyl group in the specific (meth)acrylic copolymer is 5.0 mass% or less, preferably 4.0 mass% or less, more preferably 3.0 mass% or less, even more preferably 2.0 mass% or less, and particularly preferably 1.5 mass% or less, based on the total structural units of the specific (meth)acrylic copolymer.
[0025] <Structural Unit Derived from Monomer Having a Carboxy Group> The specific (meth)acrylic copolymer does not contain any structural units derived from monomers having a carboxy group, or contains structural units derived from monomers having a carboxy group in an amount of more than 0 mass% and not more than 2.0 mass% based on the total structural units. In the present disclosure, a "structural unit derived from a monomer having a carboxy group" refers to a structural unit formed by addition polymerization of a monomer having a carboxy group.
[0026] The type of the monomer having a carboxy group is not particularly limited. An example of a monomer having a carboxy group is a monomer having at least one carboxy group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.
[0027] Specific examples of monomers having a carboxy group include acrylic acid (AA), methacrylic acid (MAA), and crotonic acid. ,MaExamples of the vinyl esters include leic acid, fumaric acid, itaconic acid, glutaconic acid, citraconic acid, ω-carboxy-polycaprolactone mono(meth)acrylates (e.g., ω-carboxy-polycaprolactone (n≒2) monoacrylate), succinic acid esters (e.g., 2-acryloyloxyethyl-succinic acid), vinyl formate, vinyl acetate, vinyl propionate, and vinyl neodecanoate.
[0028] When the specific (meth)acrylic copolymer contains a structural unit derived from a monomer having a carboxy group, the structural unit derived from the monomer having a carboxy group contained in the specific (meth)acrylic copolymer may be of only one type, or of two or more types.
[0029] The specific (meth)acrylic copolymer does not contain any structural units derived from a monomer having a carboxy group, or contains structural units derived from a monomer having a carboxy group in a range of more than 0% by mass to 2.0% by mass or less with respect to all structural units, and does not contain any structural units derived from a monomer having a carboxy group, or contains structural units derived from a monomer having a carboxy group in a range of more than 0% by mass to 1.0% by mass or less with respect to all structural units, and more preferably does not contain any structural units derived from a monomer having a carboxy group, or contains structural units derived from a monomer having a carboxy group in a range of more than 0% by mass to 0.5% by mass or less with respect to all structural units, and even more preferably does not contain any structural units derived from a monomer having a carboxy group, or contains structural units derived from a monomer having a carboxy group in a range of more than 0% by mass to 0.1% by mass or less with respect to all structural units, and particularly preferably does not contain any structural units derived from a monomer having a carboxy group. When the specific (meth)acrylic copolymer does not contain a structural unit derived from a monomer having a carboxy group, or when the specific (meth)acrylic copolymer contains a structural unit derived from a monomer having a carboxy group but contains the structural unit derived from the monomer having a carboxy group in an amount of more than 0 mass% and not more than 2.0 mass% relative to the total structural units, the pressure-sensitive adhesive layer formed tends to be less likely to corrode the transparent conductive film.
[0030] <Structural Unit Derived from (Meth)acrylic Acid Alkyl Ester Monomer> The specific (meth)acrylic copolymer preferably contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer. The structural units derived from the (meth)acrylic acid alkyl ester monomer can contribute to adjusting the adhesive strength of the pressure-sensitive adhesive layer.
[0031] In the present disclosure, the term "structural unit derived from a (meth)acrylic acid alkyl ester monomer" refers to a structural unit formed by addition polymerization of a (meth)acrylic acid alkyl ester monomer.
[0032] The type of (meth)acrylic acid alkyl ester monomer is not particularly limited. In addition, the "(meth)acrylic acid alkyl ester monomer" in the specific (meth)acrylic copolymer does not include a monomer corresponding to a monomer having a hydroxyl group and a monomer corresponding to a monomer having a carboxy group. The (meth)acrylic acid alkyl ester monomer is preferably an unsubstituted (meth)acrylic acid alkyl ester monomer. The alkyl group of the (meth)acrylic acid alkyl ester monomer may be linear, branched, or cyclic. The alkyl group preferably has 1 to 18 carbon atoms, and more preferably has 1 to 12 carbon atoms, for example.
[0033] Specific examples of the (meth)acrylic acid alkyl ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, i-nonyl (meth)acrylate, n-decyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. Among these, the (meth)acrylic acid alkyl ester monomer is preferably at least one selected from, for example, n-butyl acrylate (n-BA) and methyl acrylate (MA).
[0034] When the specific (meth)acrylic copolymer contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, it may contain only one type of structural unit derived from the (meth)acrylic acid alkyl ester monomer, or it may contain two or more types of structural units derived from the (meth)acrylic acid alkyl ester monomer.
[0035] When the specific (meth)acrylic copolymer contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer is not particularly limited, but for example, it is preferably 50 mass% or more, more preferably 50 mass% to 99.9 mass%, even more preferably 60 mass% to 99.8 mass%, even more preferably 70 mass% to 99.7 mass%, and particularly preferably 80 mass% to 99.6 mass%, relative to all structural units of the specific (meth)acrylic copolymer. Here, the content of the structural units derived from the (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer being 50 mass% or more relative to the total structural units of the specific (meth)acrylic copolymer means that the structural units derived from the (meth)acrylic acid alkyl ester monomer are contained as the main component of the structural units constituting the specific (meth)acrylic copolymer.
[0036] <Other building blocks> The specific (meth)acrylic copolymer may contain structural units (so-called other structural units) other than the structural units described above, as necessary, to the extent that the effects of the pressure-sensitive adhesive composition of the present disclosure are not impaired.
[0037] Examples of monomers constituting other structural units include aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, aromatic monovinyls such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene, vinyl cyanides such as acrylonitrile and methacrylonitrile, and vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate. Also included are various derivatives of these monomers.
[0038] When the specific (meth)acrylic copolymer contains other structural units, it may contain only one type of other structural unit, or may contain two or more types of other structural units.
[0039] When the specific (meth)acrylic copolymer contains other structural units, the content of the other structural units in the specific (meth)acrylic copolymer is not particularly limited and can be appropriately set depending on the purpose within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0040] <<Weight average molecular weight of specific (meth)acrylic copolymer>> The weight average molecular weight (also referred to as "Mw") of the specific (meth)acrylic copolymer is not particularly limited, but is, for example, preferably 1,000,000 to 3,000,000, more preferably 1,200,000 to 2,700,000, even more preferably 1,400,000 to 2,400,000, and particularly preferably 1,500,000 to 2,100,000. When the weight average molecular weight of the specific (meth)acrylic copolymer is 1,000,000 or more, the pressure-sensitive adhesive layer formed tends to have sufficiently high cohesive strength. When the weight average molecular weight of the specific (meth)acrylic copolymer is 3,000,000 or less, the viscosity does not become excessively high, and the workability during application of the pressure-sensitive adhesive composition tends to be improved.
[0041] The weight average molecular weight of the specific (meth)acrylic copolymer is a value determined by the following method, specifically, according to the following (1) to (3). (1) A solution of the specific (meth)acrylic copolymer is applied to a release paper and dried at 100° C. for 1 minute to obtain a film of the specific (meth)acrylic copolymer. (2) Using the film-like specific (meth)acrylic copolymer obtained in (1) above and tetrahydrofuran, a sample solution having a solid content concentration of 0.2% by mass is obtained. Note that the "solid content concentration" here means the mass ratio of the specific (meth)acrylic copolymer in the sample solution. (3) The weight average molecular weight of the specific (meth)acrylic copolymer is determined, in terms of standard polystyrene, by gel permeation chromatography (GPC) under the following conditions.
[0042] ~Conditions~ Measurement equipment: High-speed GPC [Model: HLC-8220 GPC, manufactured by Tosoh Corporation] Detector: Differential refractometer (RI) [installed in HLC-8220, manufactured by Tosoh Corporation] Column: TSKgel GMH XL Four Tosoh Corporation-made Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100 μL Flow rate: 0.8mL / min
[0043] The weight average molecular weight of the specific (meth)acrylic copolymer can be adjusted to a desired value by adjusting the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, amount of polymerization initiator used, etc. when polymerizing the monomer.
[0044] <<Content of specific (meth)acrylic copolymer>> The content of the specific (meth)acrylic copolymer in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but for example, it is preferably 50.0 mass% to 98.9 mass%, more preferably 60.0 mass% to 98.9 mass%, and even more preferably 70.0 mass% to 98.9 mass%, relative to the total solid content in the pressure-sensitive adhesive composition. In the present disclosure, the "total solid content in the PSA composition" means the total mass of the PSA composition when the PSA composition does not contain a solvent, and means the mass of the residue remaining after removing the solvent from the PSA composition when the PSA composition contains a solvent. In this disclosure, "solvent" means water and organic solvents.
[0045] [Method for producing specific (meth)acrylic copolymer] The method for producing the specific (meth)acrylic copolymer is not particularly limited. The specific (meth)acrylic copolymer can be produced by polymerizing the above-mentioned monomers by a known polymerization method typified by, for example, a solution polymerization method, an emulsion polymerization method, a suspension polymerization method, or a bulk polymerization method. As a polymerization method, a solution polymerization method is preferred in that the processing steps are relatively simple and can be carried out in a short time when preparing the pressure-sensitive adhesive composition of the present disclosure after production.
[0046] In the solution polymerization method, a predetermined organic solvent, a monomer, a polymerization initiator, and a chain transfer agent used as required are generally charged into a polymerization tank, and the mixture is heated and reacted for several hours with stirring at the reflux temperature of the organic solvent. In this case, at least a part of the organic solvent, the monomer, the polymerization initiator, and the chain transfer agent used as required may be added successively. The reaction may also be carried out in a nitrogen gas flow.
[0047] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, and alcohol compounds. More specifically, examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic or alicyclic hydrocarbon compounds such as n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirit, petroleum naphtha, and turpentine oil; ester compounds such as ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate; acetone, methyl ethyl acetate, and the like. Examples of the alcohol compounds include ketones, ketone compounds represented by methyl-i-butyl ketone, isophorone, cyclohexanone, and methylcyclohexanone, glycol ether compounds represented by ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether, and alcohol compounds represented by methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.
[0048] In producing the specific (meth)acrylic copolymer, it is preferable to use an organic solvent that is unlikely to cause chain transfer during the polymerization reaction, such as an aromatic hydrocarbon compound, an ester compound, or a ketone compound. In particular, it is preferable to use ethyl acetate from the viewpoints of the solubility of the specific (meth)acrylic copolymer, the ease of the polymerization reaction, and the like.
[0049] During the polymerization reaction, only one type of organic solvent may be used, or two or more types may be used.
[0050] Examples of the polymerization initiator include organic peroxides and azo compounds that are used in ordinary solution polymerization methods. Specific examples of organic peroxides include t-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-i-propyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-butyl peroxypivalate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane. Specific examples of azo compounds include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile) (ABVN), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyrate) dimethyl. In producing the specific (meth)acrylic copolymer, it is preferable to use a polymerization initiator that does not cause a graft reaction during the polymerization reaction, and it is particularly preferable to use an azo compound.
[0051] In the polymerization reaction, only one type of polymerization initiator may be used, or two or more types may be used.
[0052] The amount of the polymerization initiator used is not particularly limited, and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic copolymer.
[0053] In producing the specific (meth)acrylic copolymer, a chain transfer agent may be used, if necessary. Examples of the chain transfer agent include cyanoacetic acid, alkyl ester compounds of cyanoacetic acid having 1 to 8 carbon atoms, bromoacetic acid, alkyl ester compounds of bromoacetic acid having 1 to 8 carbon atoms, aromatic compounds such as α-methylstyrene, anthracene, phenanthrene, fluorene, and 9-phenylfluorene, aromatic nitro compounds such as p-nitroaniline, nitrobenzene, dinitrobenzene, p-nitrobenzoic acid, p-nitrophenol, and p-nitrotoluene, benzoquinone derivatives such as benzoquinone and 2,3,5,6-tetramethyl-p-benzoquinone, borane derivatives such as tributylborane, carbon tetrabromide, ... Examples of the halogenated hydrocarbon compounds include carbon chloride, 1,1,2,2-tetrabromoethane, tribromoethylene, trichloroethylene, bromotrichloromethane, tribromomethane, and 3-chloro-1-propene, aldehyde compounds such as chloral and furaldehyde, alkyl mercaptan compounds having 1 to 18 carbon atoms, aromatic mercaptan compounds such as thiophenol and toluene mercaptan, mercaptoacetic acid, alkyl ester compounds of mercaptoacetic acid having 1 to 10 carbon atoms, hydroxyalkyl mercaptan compounds having 1 to 12 carbon atoms, and terpene compounds such as pinene and terpinolene.
[0054] When a chain transfer agent is used in producing the specific (meth)acrylic copolymer, the amount of the chain transfer agent used is not particularly limited and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic copolymer.
[0055] The polymerization temperature is not particularly limited, and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic copolymer.
[0056] [Isocyanate-based crosslinking agent] The pressure-sensitive adhesive composition of the present disclosure contains an isocyanate-based crosslinking agent. The content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 4.0 parts by mass relative to 100 parts by mass of the specific (meth)acrylic copolymer.
[0057] In the present disclosure, the term "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in one molecule (so-called polyisocyanate compound).
[0058] The type of the isocyanate-based crosslinking agent is not particularly limited. Examples of the isocyanate crosslinking agent include aromatic polyisocyanate compounds such as xylylene diisocyanate (XDI), diphenylmethane diisocyanate, triphenylmethane triisocyanate, and tolylene diisocyanate (TDI), and aliphatic polyisocyanate compounds or alicyclic polyisocyanate compounds such as hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate, and hydrogenated aromatic polyisocyanate compounds. Further, examples of the isocyanate-based crosslinking agent include dimers, trimers, and pentamers of the above polyisocyanate compounds, adducts of the above polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret forms of the above polyisocyanate compounds.
[0059] As the isocyanate-based crosslinking agent, a commercially available product can be used. Examples of commercially available isocyanate crosslinking agents include "Coronate (registered trademark) HX", "Coronate (registered trademark) HL-S", "Coronate (registered trademark) L", "Coronate (registered trademark) L-45E", "Coronate (registered trademark) 2031", "Coronate (registered trademark) 2037", "Coronate (registered trademark) 2234", "Coronate (registered trademark) 2785", "Aquanate (registered trademark) 200", and "Aquanate (registered trademark) 210" (all manufactured by Tosoh Corporation), "Sumidur (registered trademark) N3300", "Desmodur (registered trademark) N3400", and "Sumidur (registered trademark) N75" (all manufactured by Sumika Covestro Urethane Co., Ltd.), "Duranate (registered trademark) E-405-80T", "Duranate (registered trademark) AE700-100", "Duranate (registered trademark) Examples of such polyurethane foams include "Duranate (registered trademark) 24A-100" and "Duranate (registered trademark) TSE-100" (all manufactured by Asahi Kasei Corporation), as well as "Takenate (registered trademark) D-110N", "Takenate (registered trademark) D-120N", "Takenate (registered trademark) M-631N", "MT-Olestar (registered trademark) NP1200", and "STABIO (registered trademark) XD-340N" (all manufactured by Mitsui Chemicals, Inc.).
[0060] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of isocyanate-based crosslinking agent, or may contain two or more types.
[0061] The content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 4.0 parts by mass with respect to 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed can suppress the shrinkage of the substrate that may occur when exposed to a high-temperature environment. The reason for this is believed to be that the crosslinking between the specific (meth)acrylic copolymer and the isocyanate-based crosslinking agent proceeds sufficiently, and the cohesive force of the pressure-sensitive adhesive layer formed is sufficiently increased. In addition, when the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to have excellent processability. From this viewpoint, the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 parts by mass or more, preferably 0.12 parts by mass or more, more preferably 0.15 parts by mass or more, and even more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 4.0 parts by mass or less relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to exhibit good adhesion to the adherend. This is thought to be because the specific (meth)acrylic copolymer and the isocyanate-based crosslinking agent are not excessively crosslinked, and the pressure-sensitive adhesive layer formed exhibits appropriate hardness. From such a viewpoint, the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 4.0 parts by mass or less, preferably 3.0 parts by mass or less, more preferably 2.0 parts by mass or less, and even more preferably 1.0 part by mass or less, relative to 100 parts by mass of the specific (meth)acrylic copolymer.
[0062] [Hydroxyl Group-Containing Tackifier] The pressure-sensitive adhesive composition of the present disclosure contains a tackifier having a hydroxyl group. The content of the tackifier having a hydroxyl group in the pressure-sensitive adhesive composition of the present disclosure is 1 part by mass to 20 parts by mass per 100 parts by mass of the specific (meth)acrylic copolymer.
[0063] In the present disclosure, the term "tackifier" refers to a compound that has the property of being able to impart tackiness when blended and has a molecular weight of less than 10,000 (preferably in the range of 500 or more and less than 10,000). Tackifiers are also called tackifiers. The tackifier in the present disclosure does not include compounds that fall under the category of specific (meth)acrylic copolymers.
[0064] The type of tackifier having a hydroxyl group is not particularly limited. Examples of tackifiers having a hydroxyl group include compounds having a rosin skeleton (e.g., rosin resins), compounds having a terpene skeleton (e.g., terpene resins), and compounds having a styrene skeleton (e.g., styrene resins). Among these, the tackifier having a hydroxyl group is preferably at least one compound selected from the group consisting of compounds having a rosin skeleton and compounds having a terpene skeleton. When the tackifier having a hydroxyl group is at least one compound selected from the group consisting of compounds having a rosin skeleton and compounds having a terpene skeleton, the pressure-sensitive adhesive layer formed tends to be able to suppress the shrinkage of the substrate that may occur when exposed to a high-temperature environment. This is thought to be because the cohesive strength of the pressure-sensitive adhesive layer is more sufficiently increased by the formation of a polymer by reaction with an isocyanate-based crosslinking agent.
[0065] Specific examples of compounds having a rosin skeleton include rosin compounds represented by abietic acid, neoabietic acid, and palustric acid, diol compounds having a rosin skeleton obtained by reacting hydrogenated rosin with diglycidyl ether, and hydrogenated rosin diol compounds. Specific examples of compounds having a terpene skeleton include copolymers of monocyclic monoterpene compounds such as α-pinene, β-pinene, and dipentene (limonene) with phenol compounds such as phenol, cresol, and bisphenol A.
[0066] As the tackifier having a hydroxyl group, a commercially available product can be used. Commercially available examples of tackifiers having hydroxyl groups include "YS Polystar T100," "YS Polystar TH130," and "YS Resin CP" manufactured by Yasuhara Chemical Co., Ltd., "Pine Crystal KE-359" and "Pine Crystal D-6011" manufactured by Arakawa Chemical Industries, Ltd., and "Sylvalite RE100XL" manufactured by AR BROWN (all of the above are trade names).
[0067] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of tackifier having a hydroxyl group, or may contain two or more types.
[0068] The content of the tackifier having a hydroxyl group in the pressure-sensitive adhesive composition of the present disclosure is 1 to 20 parts by mass relative to 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the tackifier having a hydroxyl group in the adhesive composition of the present disclosure is 1 part by mass or more per 100 parts by mass of the specific (meth)acrylic copolymer, the formed adhesive layer can suppress the shrinkage of the substrate that may occur when exposed to a high temperature environment. The reason for this is considered to be that the tackifier having a hydroxyl group incorporated between the polymer chains of the specific (meth)acrylic copolymer is likely to form a pseudo-crosslinked structure with the isocyanate-based crosslinking agent, and the cohesive force of the adhesive layer is sufficiently increased. In addition, when the content of the tackifier having a hydroxyl group in the adhesive composition of the present disclosure is 1 part by mass or more per 100 parts by mass of the specific (meth)acrylic copolymer, the formed adhesive layer tends to have excellent processability. From such a viewpoint, the content of the tackifier having a hydroxyl group in the pressure-sensitive adhesive composition of the present disclosure is 1 part by mass or more, preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 7 parts by mass or more, per 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the tackifier having a hydroxyl group in the pressure-sensitive adhesive composition of the present disclosure is 20 parts by mass or less relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to exhibit good adhesion to the adherend. The reason for this is believed to be that the tackifier having a hydroxyl group incorporated between the polymer chains of the specific (meth)acrylic copolymer does not excessively form a pseudo-crosslinked structure with the isocyanate-based crosslinking agent, and the pressure-sensitive adhesive layer formed exhibits appropriate hardness. From this viewpoint, the content of the tackifier having a hydroxyl group in the pressure-sensitive adhesive composition of the present disclosure is 20 parts by mass or less, preferably 18 parts by mass or less, more preferably 16 parts by mass or less, and even more preferably 14 parts by mass or less, relative to 100 parts by mass of the specific (meth)acrylic copolymer.
[0069] The ratio of the mass content of the tackifier having a hydroxyl group to the mass content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure (mass content of tackifier having a hydroxyl group / mass content of isocyanate-based crosslinking agent) is not particularly limited, but is, for example, preferably 2.5 to 100, more preferably 10 to 95, even more preferably 20 to 90, and particularly preferably 31 to 84. When the ratio of the mass of the tackifier having a hydroxyl group to the mass of the isocyanate crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure (mass of the tackifier having a hydroxyl group / mass of the isocyanate crosslinking agent) is 2.5 or more, the pressure-sensitive adhesive layer formed tends to exhibit better adhesion to the adherend. The reason for this is believed to be that the tackifier having a hydroxyl group incorporated between the polymer chains of the specific (meth)acrylic copolymer does not excessively form a pseudo-crosslinked structure with the isocyanate crosslinking agent, and the pressure-sensitive adhesive layer formed exhibits more appropriate hardness. When the ratio of the mass of the tackifier having a hydroxyl group to the mass of the isocyanate-based crosslinking agent in the adhesive composition of the present disclosure (mass of the tackifier having a hydroxyl group / mass of the isocyanate-based crosslinking agent) is 100 or less, the formed adhesive layer can more effectively suppress the shrinkage of the substrate that may occur when exposed to a high temperature environment. The reason for this is considered to be that the tackifier having a hydroxyl group incorporated between the polymer chains of the specific (meth)acrylic copolymer more appropriately forms a pseudo-crosslinked structure with the isocyanate-based crosslinking agent, and the cohesive force of the adhesive layer is more appropriately increased. In addition, when the ratio of the mass of the tackifier having a hydroxyl group to the mass of the isocyanate-based crosslinking agent in the adhesive composition of the present disclosure (mass of the tackifier having a hydroxyl group / mass of the isocyanate-based crosslinking agent) is 100 or less, the formed adhesive layer tends to have better processability.
[0070] [Crosslinking Accelerator] The pressure-sensitive adhesive composition of the present disclosure may further contain a crosslinking accelerator. In the pressure-sensitive adhesive composition of the present disclosure, the crosslinking accelerator can contribute to accelerating the crosslinking reaction between the hydroxyl groups in the specific (meth)acrylic copolymer and the isocyanate groups of the isocyanate crosslinking agent.
[0071] The type of crosslinking accelerator is not particularly limited. Examples of the crosslinking accelerator include imidazole compounds such as 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, and 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, organometallic compounds such as dioctyltin dilaurate and 1,3-diacetoxytetrabutylstannoxane, and tertiary amine compounds such as triethylenediamine and N-methylmorpholine. Among these, the imidazole compound is preferable as the crosslinking accelerator. It is presumed that when the adhesive composition of the present disclosure contains an imidazole compound as a crosslinking accelerator, the imidazole compound interacts with a tackifier having a hydroxyl group, and the tackifier having a hydroxyl group is easily incorporated between the polymer chains of the specific (meth)acrylic copolymer. The tackifier having a hydroxyl group incorporated between the polymer chains of the specific (meth)acrylic copolymer forms a pseudo-crosslinked structure with the isocyanate-based crosslinking agent, and therefore the cohesive strength of the adhesive layer is increased. Therefore, when the adhesive composition of the present disclosure contains an imidazole compound as a crosslinking accelerator, the adhesive layer formed tends to be able to further suppress the shrinkage of the substrate that may occur when exposed to a high-temperature environment.
[0072] As the crosslinking accelerator, commercially available products can be used. Examples of commercially available crosslinking accelerators include "Curezol (registered trademark) 1B2MZ", "Curezol (registered trademark) 1B2PZ", "Curezol (registered trademark) TBZ", and "Curezol (registered trademark) 1,2DMZ" (all trade names) manufactured by Shikoku Chemical Industry Co., Ltd.
[0073] When the pressure-sensitive adhesive composition of the present disclosure contains a crosslinking accelerator, it may contain only one type of crosslinking accelerator, or may contain two or more types of crosslinking accelerators.
[0074] When the pressure-sensitive adhesive composition of the present disclosure contains a crosslinking accelerator, the content of the crosslinking accelerator is not particularly limited, but is, for example, preferably 0.01 parts by mass to 1.5 parts by mass, more preferably 0.1 parts by mass to 1.5 parts by mass, even more preferably 0.1 parts by mass to 1.0 part by mass, and particularly preferably 0.1 parts by mass to 0.5 parts by mass, relative to 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the crosslinking accelerator in the pressure-sensitive adhesive composition of the present disclosure is 0.01 part by mass or more relative to 100 parts by mass of the specific (meth)acrylic copolymer, the crosslinking reaction between the hydroxyl groups in the specific (meth)acrylic copolymer and the isocyanate groups of the isocyanate-based crosslinking agent is promoted, and the cohesive strength of the pressure-sensitive adhesive layer formed becomes more appropriate, which tends to result in better adhesion between the pressure-sensitive adhesive layer and the substrate. When the content of the crosslinking accelerator in the pressure-sensitive adhesive composition of the present disclosure is 1.5 parts by mass or less relative to 100 parts by mass of the specific (meth)acrylic copolymer, the crosslinking accelerator is not excessively localized at the interface between the pressure-sensitive adhesive layer and the substrate, and therefore the adhesion between the pressure-sensitive adhesive layer and the substrate tends to be better.
[0075] [Plasticizer] The pressure-sensitive adhesive composition of the present disclosure may further contain a plasticizer. When the pressure-sensitive adhesive composition of the present disclosure contains a plasticizer, the adhesion between the pressure-sensitive adhesive layer and a substrate (for example, a polarizing plate) tends to be further improved.
[0076] The type of plasticizer is not particularly limited. Examples of the plasticizer include polyester-based plasticizers, phthalic acid-based plasticizers, adipic acid-based plasticizers, butadiene-based plasticizers, isoprene-based plasticizers, epoxy-based plasticizers, and liquid paraffin.
[0077] Examples of polyester plasticizers include diethylene glycol dibenzoate, triethylene glycol dibenzoate, and dipropylene glycol dibenzoate. Examples of phthalic acid plasticizers include phthalate esters such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, isobutyl phthalate, di-n-hexyl phthalate, bis(2-ethylhexyl) phthalate, bis(2-n-hexyl) phthalate, di-n-octyl phthalate, diisonoryl phthalate, dinonyl phthalate, diisodecyl phthalate, diundecyl phthalate, and bisbutylbenzyl phthalate.
[0078] Examples of the adipic acid plasticizer include adipic acid esters such as bis(2-ethylhexyl) adipate, dioctyl adipate, diisononyl adipate, and diisodecyl adipate. Examples of butadiene-based plasticizers include polybutadiene, polybutadiene having hydroxyl groups at both ends, hydrogenated polybutadiene, hydrogenated polybutadiene having hydroxyl groups at both ends, epoxidized polybutadiene, and epoxidized hydrogenated polybutadiene. Isoprene-based plasticizers include, for example, polyisoprene and hydrogenated polyisoprene. An example of an epoxy plasticizer is epoxidized soybean oil.
[0079] As the plasticizer, commercially available products can be used. Examples of commercially available plasticizers include "Liquid Paraffin" manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., "Moresco White (registered trademark) P-70" manufactured by MORESCO Corporation, "Diethylene glycol dibenzoate" manufactured by Tokyo Chemical Industry Co., Ltd., and "ADEKA CIZER (registered trademark) PN-350", "ADEKA CIZER (registered trademark) PN-446", and "ADEKA CIZER (registered trademark) PN-150" (all trade names) manufactured by ADEKA Corporation.
[0080] When the pressure-sensitive adhesive composition of the present disclosure contains a plasticizer, it may contain only one type of plasticizer, or may contain two or more types of plasticizers.
[0081] When the pressure-sensitive adhesive composition of the present disclosure contains a plasticizer, the content of the plasticizer is not particularly limited, but is, for example, preferably 0.1 parts by mass to 2.0 parts by mass, more preferably 0.3 parts by mass to 2.0 parts by mass, and even more preferably 0.5 parts by mass to 2.0 parts by mass, relative to 100 parts by mass of the specific (meth)acrylic copolymer.
[0082] [Silane coupling agent] The pressure-sensitive adhesive composition of the present disclosure may further contain a silane coupling agent. When the pressure-sensitive adhesive composition of the present disclosure contains a silane coupling agent, the adhesive strength of the pressure-sensitive adhesive layer formed to the adherend can be further improved when the adherend is glass.
[0083] The type of silane coupling agent is not particularly limited. Examples of the silane coupling agent include polymerizable unsaturated group-containing silane compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, and 3-methacryloxypropyltrimethoxysilane; thiol group-containing silane compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane; epoxy group-containing silane compounds such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane compounds such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; and tris-(3-trimethoxysilylpropyl)isocyanurate.
[0084] As the silane coupling agent, a commercially available product can be used. Examples of commercially available silane coupling agents include "KBM-803", "KBM-802", "X-41-1810", "X-41-1811", "X-41-1805", "X-41-1818", "KBM-403", "KBM-303", "KBM-402", "KBE-402", "KBE-403", "X-41-1053", "X-41-1056", "KBM-9659", "KBE-9007N", and "KBM-573" (all trade names) manufactured by Shin-Etsu Chemical Co., Ltd.
[0085] When the pressure-sensitive adhesive composition of the present disclosure contains a silane coupling agent, it may contain only one type of silane coupling agent, or may contain two or more types of silane coupling agents.
[0086] When the pressure-sensitive adhesive composition of the present disclosure contains a silane coupling agent, the content of the silane coupling agent is not particularly limited, but is, for example, preferably 0.1 parts by mass to 1 part by mass, more preferably 0.1 parts by mass to 0.8 parts by mass, and even more preferably 0.1 parts by mass to 0.5 parts by mass, relative to 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the silane coupling agent in the pressure-sensitive adhesive composition of the present disclosure is within the above range relative to 100 parts by mass of the specific (meth)acrylic copolymer, when the adherend is glass, the adhesive strength of the pressure-sensitive adhesive layer formed to the adherend can be further improved.
[0087] [Organic Solvent] The pressure-sensitive adhesive composition of the present disclosure may contain an organic solvent. When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the coatability can be further improved. As the organic solvent, for example, the same organic solvents as those used in the polymerization reaction of the above-mentioned specific (meth)acrylic copolymer can be mentioned.
[0088] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, it may contain only one type of organic solvent, or may contain two or more types of organic solvent.
[0089] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the content of the organic solvent is not particularly limited and can be set appropriately within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0090] [Other ingredients] The pressure-sensitive adhesive composition of the present disclosure may contain components other than the components described above (so-called other components) as necessary, provided that the effects of the composition are not impaired. Examples of other components include various additives such as polymers other than the specific (meth)acrylic copolymer, crosslinking agents other than isocyanate-based crosslinking agents, antioxidants, colorants (e.g., dyes and pigments), light stabilizers (e.g., ultraviolet absorbers), and antistatic agents.
[0091] When the pressure-sensitive adhesive composition of the present disclosure contains other components, the contents of the other components are not particularly limited and can be set appropriately within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0092] <<Gel fraction after crosslinking>> The pressure-sensitive adhesive composition of the present disclosure has a gel fraction after crosslinking (so-called gel fraction of the pressure-sensitive adhesive layer) of 70% by mass to 90% by mass. When the gel fraction of the pressure-sensitive adhesive composition of the present disclosure after crosslinking is 70% by mass or more, the pressure-sensitive adhesive layer formed can suppress the shrinkage of the substrate that may occur when exposed to a high-temperature environment. Also, when the gel fraction of the pressure-sensitive adhesive composition of the present disclosure after crosslinking is 70% by mass or more, the pressure-sensitive adhesive layer formed tends to have excellent processability. From this viewpoint, the gel fraction after crosslinking of the pressure-sensitive adhesive composition of the present disclosure is 70% by mass or more, preferably 73% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass or more. When the pressure-sensitive adhesive composition of the present disclosure has a gel fraction of 90 mass % or less after crosslinking, the pressure-sensitive adhesive layer formed tends to exhibit good adhesion to an adherend. From this viewpoint, the gel fraction after crosslinking of the pressure-sensitive adhesive composition of the present disclosure is 90 mass % or less, preferably 89.5 mass % or less, and more preferably 89 mass % or less.
[0093] In the present disclosure, the "gel fraction of the pressure-sensitive adhesive composition after crosslinking" refers to the proportion of solvent-insoluble matter measured using ethyl acetate as an extraction solvent. Specifically, the gel fraction of the pressure-sensitive adhesive composition after crosslinking is measured according to the following (1) to (4). (1) About 0.15 g of the crosslinked adhesive composition (i.e., adhesive layer) is attached to a 250 mesh wire net (100 mm x 100 mm) whose mass has been accurately measured using a precision balance, and the wire net is folded five times with the attached adhesive layer facing inward so as to prevent leakage of the gel, to prepare a sample. The mass of the sample is then accurately measured using a precision balance. (2) The obtained sample is immersed in 80 mL of ethyl acetate for 3 days. (3) The sample is taken out, washed with a small amount of ethyl acetate, and dried for 24 hours at 120° C. Then, the mass of the sample after this drying is accurately measured using a precision balance. (4) Calculate the gel fraction using the following formula. Gel fraction (unit: mass%) = (ZX) / (YX) x 100 where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached (unit: g) before immersion, and Z is the mass of the wire mesh with the adhesive layer attached after immersion and drying (unit: g).
[0094] <<Applications>> The application of the pressure-sensitive adhesive composition of the present disclosure is not particularly limited. The pressure-sensitive adhesive composition of the present disclosure can suppress the shrinkage of the substrate that may occur when exposed to a high-temperature environment, and can form a pressure-sensitive adhesive layer that is unlikely to corrode a transparent conductive film. The pressure-sensitive adhesive composition of the present disclosure can also form a pressure-sensitive adhesive layer that has excellent adhesion to the substrate. The pressure-sensitive adhesive composition of the present disclosure can also form a pressure-sensitive adhesive layer that has excellent processability. For this reason, the pressure-sensitive adhesive composition of the present disclosure is suitable as a pressure-sensitive adhesive composition for optical members, for example, used for optical members. The details of the optical members will be described later, and therefore will not be described here. The pressure-sensitive adhesive composition of the present disclosure is particularly suitable as a pressure-sensitive adhesive composition for use in optical members, particularly polarizing plates, and can be applied to electronic devices equipped with display devices such as liquid crystal displays and organic EL (Electro Luminescence) displays equipped with polarizing plates.
[0095] The pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure is less susceptible to corrosion of the adherend caused by carboxy groups, specifically, corrosion of the adherend by carboxylic acid, and therefore can be applied to materials other than transparent conductive films, such as those containing metals such as copper and aluminum.
[0096] [Optical components with adhesive layer] The pressure-sensitive adhesive layer-attached optical member of the present disclosure includes an optical member and a pressure-sensitive adhesive layer provided on the optical member and formed from the pressure-sensitive adhesive composition of the present disclosure. That is, in the pressure-sensitive adhesive layer-attached optical member of the present disclosure, the optical member and the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure are laminated together. The optical member with the pressure-sensitive adhesive layer of the present disclosure includes a pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure, so that the optical member is unlikely to shrink even when exposed to a high-temperature environment. Also, the optical member with the pressure-sensitive adhesive layer of the present disclosure includes a pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure, so that even when a transparent conductive film is used as an adherend, the transparent conductive film is unlikely to corrode. Also, the optical member with the pressure-sensitive adhesive layer of the present disclosure includes a pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure, so that the optical member and the pressure-sensitive adhesive layer have excellent adhesion. Also, the optical member with the pressure-sensitive adhesive layer of the present disclosure includes a pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure, so that the optical member has excellent processability.
[0097] The optical member in the pressure-sensitive adhesive layer-attached optical member of the present disclosure is not particularly limited. Examples of optical members include members constituting devices such as image display devices and input devices (so-called optical devices), and members used in these devices. Specific examples of optical members include polarizing plates, AG (Anti-Glare) polarizing plates, wave plates, retardation plates including 1 / 2, 1 / 4 and other wave plates, viewing angle compensation films, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflection films, prism sheets, lens sheets, and diffusion plates. The optical member may also be a transparent conductive film formed of, for example, ITO (indium-doped tin oxide), ATO (antimony-doped tin oxide), FTO (fluorine-doped tin oxide), tin oxide, zinc oxide, or the like.
[0098] Examples of materials for optical components include polyolefin resins (e.g., polyethylene and polypropylene), polyester resins (e.g., polyethylene terephthalate (PET)), acetate resins (e.g., triacetyl cellulose resin), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine-based resins.
[0099] As the optical member in the pressure-sensitive adhesive layer-attached optical member of the present disclosure, a polarizing plate is preferred. The polarizing plate includes at least a polarizer, and may be a single polarizer or a laminate of a polarizer and a protective film. That is, the polarizing plate may have a single-layer structure including a polarizer, a two-layer structure including a protective film on one side of the polarizer, or a three-layer structure including protective films on both sides of the polarizer. In the case where the optical member in the pressure-sensitive adhesive layer-attached optical member of the present disclosure is a polarizing plate, examples of the layer configuration include pressure-sensitive adhesive layer / polarizer, pressure-sensitive adhesive layer / polarizer / protective film, pressure-sensitive adhesive layer / protective film / polarizer / protective film, and pressure-sensitive adhesive layer / protective film / polarizer. In addition, between the polarizer and the protective film, between the protective film and the pressure-sensitive adhesive layer, and between the polarizer and the pressure-sensitive adhesive layer, layers such as retardation films (for example, optically functional layers such as an EWV layer, adhesive layers, and easy-adhesion layers) may be present. An example of the polarizer is a polyvinyl alcohol (PVA) film. Examples of the protective film include a triacetyl cellulose (TAC) film, a polycycloolefin (COP) film, a polyethylene terephthalate (PET) film, and an acrylic film.
[0100] The thickness of the pressure-sensitive adhesive layer included in the pressure-sensitive adhesive layer-attached optical member of the present disclosure is not particularly limited. The thickness of the pressure-sensitive adhesive layer is appropriately set depending on, for example, the material and shape of the adherend. The thickness of the pressure-sensitive adhesive layer is generally from 1 μm to 100 μm, preferably from 5 μm to 50 μm, and more preferably from 10 μm to 30 μm.
[0101] In the present disclosure, the "thickness of the pressure-sensitive adhesive layer" means the average thickness of the pressure-sensitive adhesive layer. The average thickness of the pressure-sensitive adhesive layer is a value measured by the following method. The arithmetic mean value of the thicknesses of the adhesive layer measured at 10 randomly selected points in the thickness direction of the adhesive layer is calculated, and the obtained value is regarded as the average thickness of the adhesive layer. The thickness of the adhesive layer is measured using a film thickness meter.
[0102] In the pressure-sensitive adhesive layer-attached optical member of the present disclosure, the exposed pressure-sensitive adhesive layer may be protected by a release film. The release film is not particularly limited as long as it can be easily peeled off from the pressure-sensitive adhesive layer, and examples include resin films that have been surface-treated with a release agent on one or both sides (so-called easy-peeling treatment). An example of the resin film is a polyester film, typically a polyethylene terephthalate (PET) film. Examples of the release agent include silicone-based release agents (eg, silicone), wax-based release agents (eg, paraffin wax), and fluorine-based release agents (eg, fluorine-based resins). The release film protects the surface of the pressure-sensitive adhesive layer until the pressure-sensitive adhesive layer-attached optical member is put to practical use, and is peeled off at the time of use.
[0103] [Method for producing an optical member with a pressure-sensitive adhesive layer] The method for producing the pressure-sensitive adhesive layer-attached optical member of the present disclosure is not particularly limited. The pressure-sensitive adhesive layer-attached optical member of the present disclosure can be produced by a known method. Examples of methods for producing an optical member with a pressure-sensitive adhesive layer of the present disclosure include the following methods. The pressure-sensitive adhesive composition of the present disclosure is applied to the easily peelable surface of a release film to form a coating film on the release film. The formed coating film is then dried to form an adhesive film on the release film. The exposed surface of the formed adhesive film is then brought into contact with an optical member and pressure is applied to transfer the adhesive film to the optical member, thereby forming an adhesive film on the optical member. The formed adhesive film is then cured to form an adhesive layer. In this manner, an optical member with a pressure-sensitive adhesive layer of the present disclosure is obtained.
[0104] Another method for producing the optical member with the pressure-sensitive adhesive layer of the present disclosure includes, for example, the following method. The pressure-sensitive adhesive composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film. Then, the formed coating film is dried to form an adhesive film on the release film. Then, the exposed surface of the formed adhesive film is placed on the easy-release treated surface of a separately prepared release film, and then pressed to produce a double-sided pressure-sensitive adhesive sheet without a substrate. Then, the adhesive film of the prepared double-sided pressure-sensitive adhesive sheet is cured to form an adhesive layer. Then, one of the two release films provided on the double-sided pressure-sensitive adhesive sheet is peeled off, and the exposed adhesive layer is brought into contact with the optical member and pressed, thereby transferring the adhesive layer to the optical member. In this manner, the optical member with the pressure-sensitive adhesive layer of the present disclosure is obtained.
[0105] Another method for producing an optical member with a pressure-sensitive adhesive layer according to the present disclosure can be, for example, the following method. The pressure-sensitive adhesive composition according to the present disclosure is applied to one surface of the optical member to form a coating film on the optical member. The coating film thus formed is then dried to form a pressure-sensitive adhesive film on the optical member. The pressure-sensitive adhesive film thus formed is then cured to form a pressure-sensitive adhesive layer. In this manner, an optical member with a pressure-sensitive adhesive layer according to the present disclosure is obtained.
[0106] The method for applying the pressure-sensitive adhesive composition is not particularly limited. Examples of methods for applying the pressure-sensitive adhesive composition include known methods using a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, knife coater, spray coater, bar coater, applicator, and the like. The amount of the adhesive composition to be applied is not particularly limited, and is appropriately set depending on, for example, the thickness of the adhesive layer to be formed.
[0107] The method for drying the coating film is not particularly limited. Examples of methods for drying the coating film include natural drying, heat drying, hot air drying, and vacuum drying. The drying temperature and drying time of the coating film are not particularly limited, and are appropriately set depending on the thickness of the coating film, the amount of the organic solvent in the coating film, and the like. An example of the drying conditions is drying using a hot air dryer at 70° C. to 120° C. for 30 to 180 seconds.
[0108] The curing is carried out, for example, for 2 to 7 days in an environment with an atmospheric temperature of 20° C. to 50° C. and a relative humidity of 45% to 55% (ie, 45% RH to 55% RH). EXAMPLES
[0109] The pressure-sensitive adhesive composition and the like of the present disclosure will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples as long as it does not deviate from the gist of the disclosure.
[0110] [Preparation of Adhesive Composition] Example 1 Into a reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser, 88.0 parts by mass of n-butyl acrylate [n-BA; acrylic acid alkyl ester monomer], 11.0 parts by mass of methyl acrylate [MA; acrylic acid alkyl ester monomer], 1.0 part by mass of 2-hydroxyethyl acrylate [2HEA; monomer having a hydroxyl group], and 80.0 parts by mass of ethyl acetate [organic solvent] were placed and mixed to obtain a mixture, and then the atmosphere inside the reactor was replaced with nitrogen. Next, the mixture in the reactor was heated to 71°C while stirring, and then 0.02 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) [ABVN; polymerization initiator] and 40.0 parts by mass of ethyl acetate were successively added to the mixture in the reactor, and after the addition was completed, the mixture was held for 6 hours to complete the polymerization reaction. Next, the solution obtained by the completion of the polymerization reaction was diluted with ethyl acetate to a solid content concentration of 15.0% by mass, and then cooled to obtain a solution of a (meth)acrylic copolymer.
[0111] The term "solid content" used herein means the mass ratio of the (meth)acrylic copolymer in the (meth)acrylic copolymer solution. The same applies to each of the (meth)acrylic copolymer solutions produced below.
[0112] 100 parts by mass (solid content equivalent) of the (meth)acrylic copolymer solution obtained above, 0.28 parts by mass (solid content equivalent) of Coronate (registered trademark) L-45E [product name, isocyanate-based crosslinking agent [adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP)], manufactured by Tosoh Corporation] as a crosslinking agent, 0.2 parts by mass (solid content equivalent) of Curesol (registered trademark) 1B2PZ [product name, manufactured by Shikoku Chemical Industries Co., Ltd.] as a crosslinking accelerator, and 10.0 parts by mass (solid content equivalent) of Pine Crystal (registered trademark) D-6011 [product name, compound having a hydroxyl group and a rosin skeleton, manufactured by Arakawa Chemical Industries Co., Ltd.] as a tackifier were thoroughly mixed to obtain a pressure-sensitive adhesive composition of Example 1.
[0113] [Examples 2 to 15] The same procedure as in Example 1 was carried out except that the composition of the adhesive composition in Example 1 was changed to the composition shown in Table 1, to obtain each of the adhesive compositions of Examples 2 to 15.
[0114] [Comparative Examples 1 to 12] The same procedure as in Example 1 was carried out except that the formulation of the adhesive composition in Example 1 was changed to the formulation shown in Table 2, to obtain each of the adhesive compositions of Comparative Examples 1 to 12.
[0115] The weight average molecular weight (Mw) of the (meth)acrylic copolymer contained in each of the pressure-sensitive adhesive compositions of Examples 1 to 15 and Comparative Examples 1 to 12 was measured, and was found to be 1.5 million in all cases. The weight average molecular weight (Mw) of the (meth)acrylic copolymer was determined by the same method as that for the weight average molecular weight (Mw) of the specific (meth)acrylic copolymer described above.
[0116] [Table 1]
[0117] [Table 2]
[0118] In Tables 1 and 2, "-" means that there is no corresponding item in that column. In Tables 1 and 2, for convenience, the "isocyanate-based crosslinking agent" and the "tackifier having a hydroxyl group" are marked with "(X)" and "(Y)", respectively, and the "ratio of the mass content of the tackifier having a hydroxyl group to the mass content of the isocyanate-based crosslinking agent" is expressed as "(Y) / (X)."
[0119] Details of each component listed in Table 1 and / or Table 2 are as follows. [(Meth)acrylic acid alkyl ester monomer] "n-BA": n-butyl acrylate "MA": Methyl acrylate [Monomer having a hydroxyl group] "2HEA": 2-hydroxyethyl acrylate [Monomer having a carboxy group] "AA": acrylic acid
[0120] [Crosslinking Agent] <Isocyanate-based crosslinking agent> "Coronate L-45E" [product name, adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP), solid content concentration: 45% by mass, manufactured by Tosoh Corporation] "Sumidur N75" [Product name, biuret of hexamethylene diisocyanate (HMDI), solid content: 75% by mass, manufactured by Sumika Covestro Urethane Co., Ltd.] <Other crosslinking agents> "TETRAD-X" [product name, epoxy crosslinking agent, solid content: 75% by mass, manufactured by Mitsubishi Gas Chemical Co., Inc.] The above "Coronate," "Sumidur," and "TETRAD" are all registered trademarks.
[0121] [Crosslinking Accelerator] "Curezol 1B2PZ" [Product name, chemical name: 1-benzyl-2-phenylimidazole, imidazole compound, manufactured by Shikoku Chemical Industry Co., Ltd.] The above "Curesol" is a registered trademark.
[0122] [Tackifier] <Tackifiers having hydroxyl groups> "Pine Crystal D-6011" [Product name, compound having a hydroxyl group and a rosin skeleton, manufactured by Arakawa Chemical Industries, Ltd.] "YS Polystar TH130" [Product name, compound with hydroxyl group and terpene skeleton, manufactured by Yasuhara Chemical Co., Ltd.] <Tackifier without Hydroxyl Group> "YS Resin PX1000" [Product name, compound with a terpene skeleton, manufactured by Yasuhara Chemical Co., Ltd.] The above "Pine Crystal" is a registered trademark.
[0123] [Plasticizer] "Liquid paraffin" [Product name: Liquid paraffin, density at 20°C: 0.825g / ml to 0.850g / ml, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.] "Diethylene glycol dibenzoate" (product name, polyester plasticizer, manufactured by Tokyo Chemical Industry Co., Ltd.)
[0124] [Silane coupling agents] "KBM-403" [Product name, chemical name: 3-glycidoxypropyltriethoxysilane, epoxy group-containing silane compound, manufactured by Shin-Etsu Chemical Co., Ltd.]
[0125] [Preparation of polarizing plate with adhesive layer] The adhesive composition prepared above was applied to the easy-release treated surface of a release film (trade name: Film Vina (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been treated to be easily peeled with a silicone-based release agent, so that the thickness after drying was 20 μm, to form a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C. and a drying time of 1 minute, to form an adhesive film on the release film. Next, the exposed surface of the formed adhesive film was laminated with one of the TAC layer surfaces of a polarizing plate having a configuration of a triacetyl cellulose (TAC) layer / polyvinyl alcohol (PVA) layer containing a polarizer / TAC layer, and then the film was left to stand for 168 hours in an environment with an atmospheric temperature of 25 ° C. and 50% RH to age the adhesive film, thereby producing a polarizing plate with an adhesive layer having a configuration of a release film / adhesive layer / polarizing plate (TAC layer / PVA layer / TAC layer).
[0126] [Measurement and Evaluation] 1. Gel fraction The gel fraction after crosslinking (i.e., the gel fraction of the pressure-sensitive adhesive layer) was measured using the pressure-sensitive adhesive composition prepared above. Specifically, it was measured by the following method. The adhesive composition prepared above was applied to the easy-release treated surface of a release film [trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.] that had been treated for easy peeling with a silicone-based release treatment agent so that the thickness after drying was 20 μm, forming a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C. and a drying time of 1 minute, forming an adhesive film on the release film. Next, the exposed surface of the adhesive film was laminated on the easy-release treated surface of a release film [trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.] that had been treated for easy peeling with a separately prepared silicone-based release treatment agent, and then left to stand for 168 hours in an environment of an atmospheric temperature of 25 ° C. and 50% RH to allow the adhesive film to mature, thereby producing a non-substrate type adhesive sheet. The pressure-sensitive adhesive sheet thus produced has a laminated structure of release film / pressure-sensitive adhesive layer / release film.
[0127] The gel fraction of the adhesive layer peeled off from the prepared adhesive sheet was then measured according to the following (1) to (4). The results are shown in Table 3. (1) About 0.15 g of the adhesive layer is attached to a 250 mesh wire net (100 mm x 100 mm) whose mass has been accurately measured using a precision balance, and the wire net is folded five times with the attached adhesive layer on the inside to prevent the gel from leaking out, to prepare a sample. After that, the mass is accurately measured using a precision balance. (2) The obtained sample is immersed in 80 mL of ethyl acetate for 3 days. (3) Take out the sample, wash it with a small amount of ethyl acetate, and dry it at 120°C for 24 hours. Then, measure the mass accurately using a precision balance. (4) Calculate the gel fraction using the following formula. Gel fraction (unit: mass%) = (ZX) / (YX) x 100 where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached before immersion (unit: g), and Z is the mass of the wire mesh with the adhesive layer attached after immersion and drying (unit: g).
[0128] 2. Shrinkage of polarizing plates (1) Preparation of samples for shrinkage evaluation The polarizing plate with the adhesive layer prepared above was cut so that the long side was at 0° with respect to the absorption axis, and a test piece with a size of 66 mm x 136 mm (long side) was prepared. Next, the release film of the test piece was peeled off, and the surface of the adhesive layer exposed by the peeling was placed on one side of blue plate (soda) glass (manufactured by Matsunami Glass Industry Co., Ltd.), and then pressed with a laminator to prepare a laminate. Next, the prepared laminate was autoclaved (treatment temperature: 50°C, treatment pressure: 5 kg / cm2). 2 (treatment time: 20 minutes) was applied to prepare a sample for shrinkage evaluation.
[0129] (2) Evaluation test The sample for shrinkage evaluation prepared above was left to stand in a high temperature environment of 85°C for 168 hours. The length of the long side (i.e., the side at 0° to the absorption axis) of the sample for shrinkage evaluation after standing was measured using a digital microscope, and the shrinkage rate was calculated using the following formula. Evaluation was then performed according to the following evaluation criteria. The results are shown in Table 3. Shrinkage rate (unit: %) = [[Length of the long side of the sample for evaluating shrinkage before standing (unit: mm)] - [Length of the long side of the sample for evaluating shrinkage after standing (unit: mm)]] / Length of the long side of the sample for evaluating shrinkage before standing (unit: mm) x 100
[0130] A smaller value of the shrinkage rate indicates that the pressure-sensitive adhesive layer effectively suppresses the shrinkage of the polarizing plate. In the following evaluation criteria, "A" and "B" are at levels that are not problematic in practical use, with "A" being the most preferable.
[0131] -Evaluation criteria- A: The shrinkage rate is 0.40% or less. B: The shrinkage rate is in the range of more than 0.40% and 0.55% or less. C: The shrinkage rate exceeds 0.55%. D: The gel fraction did not increase sufficiently, so evaluation was impossible, or peeling occurred, so measurement was impossible.
[0132] 3. Adhesion to polarizing plate (1) Preparation of samples for adhesion evaluation The polarizing plate with the adhesive layer prepared above was cut so that the long side was at 0° with respect to the absorption axis, and a test piece with a size of 25 mm x 75 mm (long side) was prepared. Next, the release film of the test piece was peeled off, and the surface of the adhesive layer exposed by peeling was placed on one side of a stainless steel plate [product name: SUS304 (BA), manufactured by Paltec Co., Ltd.], and then pressed with a laminator to prepare a laminate. Next, the prepared laminate was autoclaved (treatment temperature: 50°C, treatment pressure: 5 kg / cm 2 (treatment time: 20 minutes) was then applied. Next, the laminate after autoclave treatment was left to stand for 4 hours in an environment with an atmospheric temperature of 50° C. to prepare a sample for adhesion evaluation.
[0133] (2) Evaluation test For the adhesion evaluation sample prepared above, a single column type material testing machine (model number: STA-1225) made by A&D Co., Ltd. was used to peel the test piece (structure: adhesive layer / polarizing plate (TAC layer / PVA layer / TAC layer)) from the adherend (SUS) at 180° in the long side (75 mm) direction under the conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. Evaluation was then performed according to the following evaluation criteria. The results are shown in Table 3. In the following evaluation criteria, "A" and "B" are at levels that are not problematic in practical use, with "A" being the most preferable.
[0134] -Evaluation criteria- A: The adhesive layer has not been transferred to the SUS at all. B: A small amount of the adhesive layer has been transferred to the SUS, but this is at a level that does not cause any practical problems. C: The adhesive layer was transferred to the SUS, and this was at a level that was problematic for practical use. D: The gel fraction does not increase sufficiently, so evaluation is not possible.
[0135] 4. Corrosion of ITO film (1) Preparation of samples for corrosion evaluation The adhesive composition prepared above was applied to the easy-release treated surface of a release film (trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been treated for easy peeling with a silicone-based release agent so that the thickness after drying was 20 μm, forming a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C. and a drying time of 1 minute, forming an adhesive film on the release film. Next, the exposed surface of the adhesive film was laminated and attached to the surface of a separately prepared PET film (trade name: Ester HPE, manufactured by Toyobo Film Solutions Co., Ltd.), and then left to stand for 168 hours in an environment with an atmospheric temperature of 25 ° C. and 50% RH to allow the adhesive film to mature, thereby producing an adhesive sheet. The produced adhesive sheet has a laminated structure of release film / adhesive layer / substrate (PET). The adhesive sheet thus prepared was then cut to a size of 80 mm × 100 mm to obtain an adhesive sheet piece. The release film of the obtained adhesive sheet piece was peeled off, and the surface of the adhesive layer exposed by the peeling was placed on the ITO film surface of an ITO-coated glass (size: 100 mm × 100 mm, manufactured by Geomatec Co., Ltd.), and then pressed with a 2 kg roller to produce a laminate, which was used as a corrosion evaluation sample.
[0136] (2) Evaluation test The sheet resistance value (unit: Ω / sq.) of the ITO film of the corrosion evaluation sample prepared above was measured using a tester (product name: card-type digital multimeter MT-4081J, manufactured by Mother Tools Co., Ltd.). The measured value obtained was taken as the initial value. Next, the corrosion evaluation sample was left to stand for 2 weeks in an environment of 60°C and 95% RH. After standing, the sheet resistance value (unit: Ω / sq.) of the ITO film was measured using a tester (product name: card-type digital multimeter MT-4081J, manufactured by Mother Tool Co., Ltd.) to determine the rate of change (unit: %) from the initial value. Evaluation was then performed according to the following evaluation criteria. The results are shown in Table 3. The smaller the rate of change in sheet resistance, the less likely the adhesive layer is to corrode the ITO film. In the following evaluation criteria, "A" is a level that is not problematic in practical use.
[0137] -Evaluation criteria- A: The rate of change in sheet resistance is 5.0% or less. B: The rate of change in sheet resistance value exceeds 5.0%. C: The gel fraction does not increase sufficiently, so evaluation is not possible.
[0138] 5. Processability (1) Preparation of samples for processability evaluation The processability of the pressure-sensitive adhesive layer was evaluated by a holding power test (so-called creep evaluation) in accordance with JIS Z 0237: 2009. Specifically, the evaluation was performed by the following method. The adhesive composition prepared above was applied to the easy-release treated surface of a release film (trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been treated for easy peeling with a silicone-based release agent so that the thickness after drying was 20 μm, forming a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C. and a drying time of 1 minute, forming an adhesive film on the release film. Next, the exposed surface of the adhesive film was laminated and bonded to the surface of a separately prepared PET film (trade name: Ester HPE, manufactured by Toyobo Film Solutions Co., Ltd.), and then left to stand for 168 hours in an environment with an atmospheric temperature of 25 ° C. and 50% RH to allow the adhesive film to mature, thereby producing an adhesive sheet. The produced adhesive sheet has a laminated structure of release film / adhesive layer / substrate (PET). The prepared adhesive sheet was then cut to a size of 25 mm x 75 mm to obtain an adhesive sheet piece. The release film of the obtained adhesive sheet piece was peeled off, and the surface of the adhesive layer exposed by peeling was placed on one side of blue plate (soda) glass (manufactured by Matsunami Glass Industry Co., Ltd.) so that the bonding area was 25 mm x 25 mm, and then pressed with a 2 kg roller to prepare a laminate. The prepared laminate was then subjected to autoclave treatment (treatment temperature: 50°C, treatment pressure: 5 kg / cm2, treatment time: 20 minutes) to obtain a sample for processability evaluation.
[0139] (2) Evaluation test A mark was made in advance on the glass portion of the sample for evaluating processability where the adhesive sheet piece X [structure: adhesive layer / base material (PET)] was not attached. The sample for evaluating processability was held so that the glass was normal to the ground and the unattached portion of the adhesive sheet piece X was facing down, and a 1 kg weight was attached to the unattached portion of the adhesive sheet piece X and hung, and the sample was left for 1 hour in an environment with an atmospheric temperature of 25°C and 50% RH. After leaving the sample, the weight of the adhesive sheet piece X was removed, and the movement distance (unit: μm) of the adhesive sheet piece X before and after leaving the sample was measured using a digital microscope based on the mark made in advance on the glass. Evaluation was then performed according to the following evaluation criteria. The results are shown in Table 3. In the following evaluation criteria, "A" and "B" are at levels that are not problematic in practical use, with "A" being the most preferable. The shorter the travel distance of the adhesive sheet piece X, the harder the adhesive layer is, and the less likely it is that the adhesive layer (so-called glue) will stick to the cutting blade or that the adhesive layer will protrude during cutting, indicating excellent processability.
[0140] -Evaluation criteria- A: The movement distance of the adhesive sheet piece X is 20 μm or less. B: The movement distance of the adhesive sheet piece X is in the range of more than 20 μm and 30 μm or less. C: The moving distance of the adhesive sheet piece X exceeds 30 μm. D: The gel fraction does not increase sufficiently, so evaluation is not possible.
[0141] [Table 3]
[0142] As shown in Table 3, it was found that the pressure-sensitive adhesive layers formed by the pressure-sensitive adhesive compositions of Examples 1 to 15 can suppress the shrinkage of the polarizing plate that may occur when exposed to a high-temperature environment, and are less likely to corrode the ITO film, which is a transparent conductive film. It was also found that the pressure-sensitive adhesive layers formed by the pressure-sensitive adhesive compositions of Examples 1 to 15 have excellent adhesion to the polarizing plate, which is the substrate. It was also found that the pressure-sensitive adhesive layers formed by the pressure-sensitive adhesive compositions of Examples 1 to 15 have excellent processability.
[0143] On the other hand, the adhesive layer formed from the adhesive composition of Comparative Example 1, in which the content of structural units derived from monomers having a hydroxyl group in the (meth)acrylic copolymer was less than 0.1 mass% relative to the total structural units, did not have a sufficiently high gel fraction and could not be subjected to evaluation testing. The adhesive layer formed from the adhesive composition of Comparative Example 2, in which the content of structural units derived from monomers having a hydroxyl group in the (meth)acrylic copolymer exceeded 5.0 mass% relative to the total structural units, peeled off from the soda lime glass, making it impossible to perform an evaluation test for the shrinkage of the polarizing plate. The adhesive layer formed from the adhesive composition of Comparative Example 3, in which the content of the crosslinking agent was less than 0.1 parts by mass per 100 parts by mass of the (meth)acrylic copolymer, did not have a sufficiently high gel fraction and could not be subjected to evaluation tests. The adhesive layer formed from the adhesive composition of Comparative Example 4, in which the content of crosslinking agent exceeded 4.0 parts by mass per 100 parts by mass of the (meth)acrylic copolymer, peeled off from the soda lime glass, and therefore it was not possible to perform an evaluation test for the shrinkage of the polarizing plate. The pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 5, in which the content of the tackifier having a hydroxyl group was less than 1 part by mass per 100 parts by mass of the (meth)acrylic copolymer, was unable to suppress the shrinkage of the polarizing plate. In addition, it was found that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 5 was inferior in processability to the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of the Examples. The adhesive layer formed from the adhesive composition of Comparative Example 6, in which the content of tackifier having a hydroxyl group exceeded 20 parts by mass per 100 parts by mass of the (meth)acrylic copolymer, peeled off from the soda lime glass, and therefore it was not possible to perform an evaluation test for the shrinkage of the polarizing plate. The pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 7, which had a gel fraction of less than 70% by mass, was unable to suppress the shrinkage of the polarizing plate. In addition, it was found that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 7 was inferior in processability to the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of the Examples. The adhesive layer formed from the adhesive composition of Comparative Example 8, in which the gel fraction after crosslinking exceeded 90% by mass, peeled off from the soda lime glass, and therefore it was not possible to carry out a test to evaluate the shrinkage of the polarizing plate. The pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 9, which had a gel fraction of less than 70% by mass after crosslinking, was unable to suppress the shrinkage of the polarizing plate. It was also found that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 9 was inferior in processability to the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of the Examples. The pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 10, which contained a tackifier without a hydroxyl group instead of a tackifier with a hydroxyl group, was unable to suppress the shrinkage of the polarizing plate. It was also found that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 10 was inferior in processability to the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of the Examples. It was found that the adhesive layer formed from the adhesive composition of Comparative Example 11, in which the content of structural units derived from monomers having a carboxy group in the (meth)acrylic copolymer exceeded 2.0 mass% relative to the total structural units, was prone to corroding the ITO film, which is a transparent conductive film. The adhesive layer formed from the adhesive composition of Comparative Example 12, which contained an epoxy-based crosslinking agent instead of an isocyanate-based crosslinking agent, did not have a sufficiently high gel fraction and could not be subjected to evaluation tests.
Claims
1. a (meth)acrylic copolymer containing 0.1% by mass to 5.0% by mass of structural units derived from monomers having a hydroxyl group relative to all structural units, and not containing structural units derived from monomers having a carboxy group, or containing structural units derived from monomers having a carboxy group in an amount of more than 0% by mass to 2.0% by mass or less relative to all structural units; An isocyanate-based crosslinking agent; A tackifier having a hydroxyl group; Including, the content of the isocyanate-based crosslinking agent is 0.1 parts by mass to 4.0 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer; the content of the tackifier having a hydroxyl group is 1 part by mass to 20 parts by mass based on 100 parts by mass of the (meth)acrylic copolymer, The gel fraction after crosslinking is 70% by mass to 90% by mass, A pressure-sensitive adhesive composition for optical members, which is used for forming a pressure-sensitive adhesive layer provided on an optical member.
2. 2. The pressure-sensitive adhesive composition for optical members according to claim 1, wherein a ratio of a content by mass of the tackifier having a hydroxyl group to a content by mass of the isocyanate-based crosslinking agent is 2.5 to 100.
3. 3. The pressure-sensitive adhesive composition for optical members according to claim 1, wherein the tackifier having a hydroxyl group is at least one compound selected from the group consisting of compounds having a rosin skeleton and compounds having a terpene skeleton.
4. The pressure-sensitive adhesive composition for optical members according to any one of claims 1 to 3, further comprising a plasticizer.
5. The pressure-sensitive adhesive composition for optical members described in any one of claims 1 to 4, further comprising a silane coupling agent.
6. The pressure-sensitive adhesive composition for optical members described in any one of claims 1 to 5, further comprising a crosslinking accelerator, wherein the crosslinking accelerator is an imidazole compound.
7. An optical member; a pressure-sensitive adhesive layer provided on the optical member and formed from the pressure-sensitive adhesive composition for optical members according to any one of claims 1 to 6; An optical member with a pressure-sensitive adhesive layer comprising:
Citation Information
Patent Citations
Ionizing radiation-curing removable adhesive composition
JP2010235856A
Adhesive tape for sealing food container
JP2013163746A
Removable aqueous adhesive and adhesive sheet
JP2015117347A
Adhesive tape
JP2018141086A
Adhesive composition for optical components, adhesive layer for optical components and method for manufacturing the same, adhesive-coated optical component, and image display device.
JP4485329B2
